The Bhutanese gompa at Swayambhu: sketches and notes from the Musée Guimet’s Hodgson Collection of Deva Dharma Maha Vihar - S Shiriin Barakzai (European Bulletin of Himalayan Research)
This article describes two sketches and three pages of Sanskrit notes kept in the Musée Guimet’s Hodgson Collection. The titles of the sketches suggest that these are of a temple to the west of Swayambhu mahacaitya, Kathmandu, currently under Bhutanese management and known as Dongag Choling. A description of the sketches and a translation of the attached notes attached to sketch no32 are provided here based on photographs shared by the Guimet during the COVID-19 lockdown. Even prior to the 2015 Gorkha earthquake, after which the temple was completely reconstructed, the wall paintings suggested by the sketches were no longer extant. The sketches are compared with an 1885 sketch by Oldfield and with the current structure to understand how the temple has evolved structurally. The comparison with Oldfield’s sketch suggests that this identification of the temple is correct and that a reconstruction following the 1907 fire led to significant changes, not only to the overall structure, but to the interior decoration. It cannot be ascertained, based on the scanned images of the sketches, whether or not the temple was under Bhutanese control at the time these were drawn, thus referral to the full set of original sketches is still required.